Management of Nursing Care for Patients at Risk of Violent Behavior with Implementation Strategies to Control Anger in the Mental Hospital - Andriany, Rizky; Sari, Sheni Mutiara; Moulisya, Deca Gardena (International Journal Scientific and Professional, 2023)
The risk of violent behavior is a situation where a person commits an action that can harm himself or herself or others or the environment, whether physically, emotionally, sexually or verbally, accompanied by uncontrolled rage and restless noise. The purpose of this paper is to describe the management of nursing care for patients at risk of violent behavior in mental hospitals. The method that will be used is the descriptive method by implementing nursing for 6 days in the form of nursing care for clients to meet the need for preventing the risk of violent behavior by providing the application of controlling emotions with SP 1 to 5. The data collection technique is carried out using a nursing methodology approach which consists of build relationships of mutual trust and carry out assessments which include physical examination, observation, supporting examinations, enforcement of nursing diagnoses, nursing interventions, nursing implementation and nursing evaluation. The results of nursing management showed that the problem of risk of violent behavior was resolved because the client was able to control anger by applying SP 1 to SP 5, namely by deep breathing relaxation, by hitting a pillow or mattress, verbally, by praying and by obediently taking medication. Try not to cause other problems due to the risk of violent behavior. Suggestions for nurses in hospitals to continue to teach and provide education on how to control anger to clients who are at riskof violent behaviour independently.